ANALISIS EFISIENSI PEMASARAN JAMUR TIRAM SEGAR (STUDI KASUS DI KECAMATAN NGARGOYOSO) - MAHANANTO MAHANANTO; KUSRIANI PRASETYOWATI (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2019)
analyzing chain and function of marketing, analyzing structure and behavior of market, and analyzing efficincy marketing. This research was designed case study. This research conducted in Ngargoyoso, Karanganyar, central Java. Sampling was done: producer (farmer) sampel with judgement technique, marketing institution and market location with snow ball and accidental sampling. The analysis instrument used descriptive, margin of marketing, farmer share and profit cost rasio. The result of this research: marketing institution was involved: producer, pengepul (bring together), big trader, small trader and retailer. The chain marketing are: producer to consumer, producer to pengepul (bring together) to big trader to consumer, producer to pengepul (bring together) to big trader to small trader to consumer, and producer to pengepul (bring together) to big trader to small trader to retailer to consumer. The functions marketing are: producer selling, transportasion and packaging, grading and standartsation, pengepul (bring together) buying and selling, transportasion and packaging, grading and standartsation, big trader buying and selling, transportasion and packaging, grading and standartsation, small trader buying and selling, transportasion and packaging, grading and standartsation, retailer buying and selling, transportasion and packaging. The market structure are: producer and pengepul (bring together) olygopsony, pengepul and big trader perfect competition, big trader and small trader oligopoly, small trader and retailer perfect competition, retailer and consumer perfect competition. The most efficientcy marketing producer to consumer (farmar share 100%).